CODE SWITCHING IN ARTICLES IN THE JAKARTA POST - Bria, Maria Gaudensia; Kasmiran, Marselus Suarta; Bram, Barli (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
This paper explored code switching between English and Indonesian in articles in the daily newspaper The Jakarta Post. Data were collected from six articles published in The Jakarta Post. The code switching data were analyzed to determine the reasons for the writers to switch codes. Results showed that there existed five reasons for code switching, namely â€œlack of one word in either language, one wants to make a point, some activities have only been experienced in one of the languages, some words are easier, more distinguishable and easier to use in one of the languages, and the speaker has difficulty in expressing oneself: expressing group identityâ€. Related to the educational field, it is expected that the results will be beneficial for English teachers or lecturers to be more aware that sometimes they cannot avoid using code switching because translating some Indonesian words into English will lose the essence of the meaning.